1997
DOI: 10.1016/s0014-5793(97)01383-5
|View full text |Cite
|
Sign up to set email alerts
|

Detection and cloning of unique integration sites of retrotransposon, intracisternal A‐particle element in the genome of acute myeloid leukemia cells in mice1

Abstract: We previously found retrotransposition of the intra-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
8
0
1

Year Published

2001
2001
2014
2014

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 17 publications
0
8
0
1
Order By: Relevance
“…Active role of I⌬1-type IAP protein in trans-complementation IAP-transposition has been reported in both germ cells and somatic tissues (Ishihara and Tanaka 1997;Maksakova et al 2006). In both cases, most of the transposed elements were I⌬1 type with an internal deletion that results in in-frame fusion of gag-pol genes (Kuff and Lueders 1988).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Active role of I⌬1-type IAP protein in trans-complementation IAP-transposition has been reported in both germ cells and somatic tissues (Ishihara and Tanaka 1997;Maksakova et al 2006). In both cases, most of the transposed elements were I⌬1 type with an internal deletion that results in in-frame fusion of gag-pol genes (Kuff and Lueders 1988).…”
Section: Resultsmentioning
confidence: 99%
“…A previous study reported frequent IAP-transposition in radiation-induced mouse acute myeloid leukemia (AML) (Ishihara and Tanaka 1997). We hypothesized that IAP-transposition in AML may provide a unique experimental system to investigate the regulatory mechanisms of retrotransposon proliferation.…”
mentioning
confidence: 99%
“…Although the full-length type constitutes 70% of the entire IAP population in the mouse genome (Kuff and Lueders 1988), mostly ID1 type were found as a causative insertion of spontaneous mutant mice (Maksakova et al 2006), consistent with the predominance of ID1 type in our analysis of AML cells. The full-length IAP element, designated as Q14 (Ishihara and Tanaka 1997), retained the open reading frames of gag, pro, and pol genes, suggesting that it is an autonomous IAP element. We therefore isolated the Q14 IAP element from the AML genome and inserted an indicator GFP cassette that contains an intron in the antisense orientation relative to the GFP gene (Ostertag et al 2000) (Figure 1A).…”
Section: Resultsmentioning
confidence: 99%
“…We have previously reported a high frequency of IAP retrotransposition in radiation-induced mouse acute myeloid leukemia (AML) in C3H/He mice (Ishihara and Tanaka 1997) and identified eight IAP elements that retrotransposed during AML formation (Ishihara et al 2004). We hypothesized that these retrotranspositioncompetent IAP elements could be useful tools for studying the direct effect of retrotransposition on the genome.…”
mentioning
confidence: 99%
“…30,39,40,50 IAP insertions have been observed during cultivation of mouse hematopoietic stem cell lines and in mouse tumor cells. [51][52][53][54] Engineered L1 elements can retrotranspose when introduced into human ES cells, human and rat neural progenitor cells, human oocytes, primary human fibroblasts, a variety of cancer cell lines, and retrotranspose at higher levels in response to oxidative stress and ionizing radiation. [29][30][31]36,[55][56][57][58][59] The extent of ongoing retrotransposition in mammals…”
mentioning
confidence: 99%